Long-Noncoding RNA PCAT6 Aggravates Osteosarcoma Tumourigenesis via the MiR-143-3p/ZEB1 Axis - Wu K (OncoTargets and Therapy, 2020)
Kai Wu,1,* Qiong Feng,2,* Liang Li,1 Yanfei Xiong,3 Shihong Liu,4 Jie Liu,1 Qing Wu1 1Department of Orthopedics, The Second Affiliated Hospital of Nanchang University, Nanchang 300006, People’s Republic of China; 2Nursing School, Nanchang University, Nanchang 300006, People’s Republic of China; 3Department of Orthopedics, Jingan Hospital, Yichun 330600, People’s Republic of China; 4Jingan Hospital of Traditional Chinese Medicine, Yichun 330600, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qing Wu Email wuqing18186@126.comIntroduction: The long-noncoding RNA PCAT6 plays an important regulatory role in the development of several cancers. However, the expression pattern and underlying mechanisms of PCAT6 in osteosarcoma (OS) are yet unknown.Methods: We used real-time PCR to measure PCAT6 expression in 106 tumor pairs and corresponding non-tumor tissues from OS patients. Statistical analyses were applied to evaluate the prognostic value and associations of PCAT6 expression with clinical parameters. Furthermore, the PCAT6 was silenced with siRNA in OS cells. Moreover, phenotype of PCAT6 silenced OS cells was measured using colony formation, CCK-8, cell migration and invasion assay. Finally, the molecular mechanism of PCAT6/miR-143-3p/ZEB1 axis in OS progression was explored.Results: The expression level of PCAT6 in OS tissues was significantly elevated as compared with that in the adjacent normal bone tissues and that high PCAT6 expression closely correlated with the malignant phenotype and poor survival among patients with OS. Multivariate analyses revealed PCAT6 overexpression as an independent prognostic factor for the poor outcome of patients with OS. Functional assay results demonstrated that the knockdown of PCAT6 expression notably suppressed the proliferation, migration, and invasion of OS cells. An elevated PCAT6 level aggravated the malignant phenotype of OS cells via ZEB1 expression upregulation. Mechanistic studies revealed that PCAT6 could sponge endogenous miR-143-3p and inhibit its activity, resulting in an increase in ZEB1 level. Finally, we demonstrated that the tumour-promoting role of PCAT6 in OS was dependent on the regulation of the miR-143-3p/ZEB1 axis.Conclusion: These findings highlight the potential role of PCAT6, which could serve as a valuable prognostic indicator for patients with OS.Keywords: osteosarcoma, PCAT6, ZEB1, miR-143-3p